Thermodynamic Behaviour of Hypersensitive Transitiond Observed in Some Pr3+ and Nd3+ Doped Pharmaceutical Compounds - Aryamitra Pandey, Ms.; Tater, P.C.; Soni, K.P.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The saturated anionic ligand environment produced by various pharmaceutical compounds, viz., thiabendazole, mebendazole, albendazole and diethylcarbamazine in alcohol around Pr3+ and Nd3+ ions has been studied with respect to the hypersensitive transition involved in the system. The spectroscopic data for the hypersensitive transition has been correlated with the thermodynamic parameters (work function and thermodynamic efficiency) which yield the thermodynamic behaviour of the said transition.